Laparoscopic management of bladder ectopic pregnancy - Shahul Hameed Mohamed Siraj; Bernard Su Min Chern (Wolters Kluwer Medknow Publications, 2016)
Ectopic pregnancy is a potentially life-threatening condition and still the major cause of maternal mortality in the first trimester of pregnancy. It accounts for approximately 10% of maternal deaths. The involvement of the urinary tract is rare, usually occurring after the rupture of an abdominal implanted ectopic embryonic sac. We herein present a case of an ectopic pregnancy implanted in the bladder and successful laparoscopic management. To the best of our knowledge, this is the first description of abdominal pregnancy on the bladder wall in a natural cycle and successful laparoscopic management.